PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI MATERI PLANTAE BERBASIS INKUIRI TERBIMBING TERINTEGRASI NILAI ISLAM UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA SMA - Hanif Hanif; Ibrohim Ibrohim; Fatchur Rohman (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
The development research aims to produce learning materials Plantae such as devices based Guided Inquiry integrated Islamic values to improved understanding of the concept of high school students. Adapted development the procedure development according the Borg and Gall model. The results of the analysis of the learning device shows the value of the average percentage of expert learning device by 98.1%, 86.1% materials experts and teachers of 95.4%. Small groups of test results by 89.8%. The main test was conducted on the experimental class and the control class in high school Annur Bululawang. The results of data analysis using Anacova showed that the understanding of the concept of students in the experimental class is significantly different from the students in the control class. Scores understanding of the concept of students in the experimental class is higher (80.9) than the control group (67.5). The results of this study indicate that the application of Guided Inquiry-based learning device can significantly increase students' understanding of the concept.Penelitian pengembangan ini bertujuan untuk menghasilkan produk berupa perangkat pembelajaran materi Plantae berbasis Inkuiri Terbimbing terintegrasi nilai Islami dalam peningkatan pemahaman konsep siswa SMA. Prosedur pengembangan mengadaptasi model pengembangan Borg and Gall. Hasil analisis perangkat pembelajaran menunjukkan nilai persentase rata-rata dari ahli perangkat pembelajaran sebesar 98,1%, ahli materi 86,1%, dan guru sebesar 95,4%. Hasil uji kelompok kecil sebesar 89,8%. Uji coba utama dilakukan pada satu kelas eksperimen dan satu kelas kontrol di SMA Annur Bululawang. Hasil analisis data menggunakan anakova menunjukkan bahwa pemahaman konsep siswa di kelas eksperimen berbeda secara signifikan dengan siswa di kelas kontrol. Skor pemahaman konsep siswa pada kelas ekperimen lebih tinggi (80,9) daripada kelas kontrol (67,5). Hasil penelitian ini menunjukkan bahwa penerapan perangkat pembelajaran berbasis Inkuiri Terbimbing secara signifikan mampu meningkatkan pemahaman konsep siswa.